2019
DOI: 10.1021/acs.jpcc.9b07641
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Friendly and Safe Method of Fabricating Superhydrophobic Surfaces on Stainless Steel Substrates

Abstract: Industries are forced to explore more eco-friendly and safer processing methods to cope with increasing environmental issues. One of them is the fabrication of superhydrophobic stainless steel surfaces in the food industry. Current methods of fabricating superhydrophobic stainless steel surfaces have disadvantages, including using various toxic chemicals and fluorinated modifications, which cause hazards and environmental pollution, thereby limiting the application in the food industry. In this paper, an eco-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 42 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…[ 82 ] In addition, superhydrophobic stainless steel was also fabricated through vacuum evaporation of copper film, chemical deposition of Ag, and heat treatment at 100 °C, which possessed a WCA of 155.7° and a WSA of close to 0° exhibiting resistance to acid and alkali and a self‐cleaning property. [ 83 ]…”
Section: Solution Immersion Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 82 ] In addition, superhydrophobic stainless steel was also fabricated through vacuum evaporation of copper film, chemical deposition of Ag, and heat treatment at 100 °C, which possessed a WCA of 155.7° and a WSA of close to 0° exhibiting resistance to acid and alkali and a self‐cleaning property. [ 83 ]…”
Section: Solution Immersion Methodsmentioning
confidence: 99%
“…[82] In addition, superhydrophobic stainless steel was also fabricated through vacuum evaporation of copper film, chemical deposition of Ag, and heat treatment at 100 C, which possessed a WCA of 155.7 and a WSA of close to 0 exhibiting resistance to acid and alkali and a self-cleaning property. [83] In 2012, to obtain rough nickel arrays, Kang et al [84] immersed etched porous aluminum substrates into a mixed solution containing lactic acid, NaH 2 PO 2 •H 2 O, CH 3 COONa, NaHCO 3 , and NiSO 4 •6H 2 O to deposit nickel nanoparticles. And then, superhydrophobic nickel surfaces with WCA of 164 AE 2 were acquired by modifying by 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane.…”
Section: Chemical Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…It indicated that the surface had good self‐cleaning property. To reduce environmental pollution caused by chemical reagents, Wang et al [ 70 ] produced SHPB surfaces on stainless steels by an eco‐friendly and safe method. Micro–nano structures were formed through vacuum evaporation as well as chemical reaction.…”
Section: Applications In Architectural Engineeringmentioning
confidence: 99%
“…However, the water contact angle on the smooth hydrophobic surface generally does not exceed 125 o [8,9]. Nowadays, studies involving the preparation of superhydrophobic surfaces (lignocellulose nanofibrils [10], stainless steel [11], wood [12]... etc) suitable for the purpose of use are quite attractive. Superhydrophobic surfaces (> 150 o ) can be obtained by controlling the surface roughness via various processing methods, such as etching [13,14], drop evaporation [15], a gel-like porous coating [16] and spin-coating of nanoparticles dispersed in an organic solvent onto polymeric films [17].…”
Section: Introductionmentioning
confidence: 99%